ANALYSIS OF INVESTMENT ATTRACTIVENESS OF KAZAKHSTAN - A. B. Amerkhanova (Academic Journal of Physical and Chemical Sciences, 2019)
The Republic of Kazakhstan is attractive for investors. The factors that ensure the investment attractiveness of the Kazakhstan market include: access to natural resources, market size, strategic location of Kazakhstan, as well as a stable political situation and the availability of an appropriate legislative framework. In the article the rating of investment attractiveness of Kazakhstan and favorable conditions for investors are considered. The problems and negative factors in the field of attracting investments are identified. It is proposed to stimulate the development of competitive industries by using more actively such proven tools in world practice as special economic and industrial zones, social and entrepreneurial corporations, launching IPO by Kazakhstani companies and the development of the securities market, based on the favorable business climate of Kazakhstan.